Influence of Habesha eggshell on the dry sliding wear behavior of epoxy composites - Shahapurkar K.; Ramesh S.; Nik-Ghazali N.-N.; Chenrayan V.; MC K.; Kanaginahal G.; Soudagar M.E.M.; Fouad Y.; M.A.Kalam (Springer Science and Business Media Deutschland GmbH, 2025)
Increased waste generation and disposal have become serious concerns in terms of landfill burden and environmental pollution. Transforming the waste materials into useful ones by recycling or reprocessing is the right solution to address the challenges. Eggshells are one sort of bio-waste that has had a significant impact on the material market, which is in desperate need of lightweight, wear-resistant materials. Present research uses Habesha eggshells derived from Ethiopia to process the novel epoxy composite with improved tribo-properties. The open-cast mold technique is employed to fabricate epoxy composites with varying vol.% of Habesha eggshell particles in 5, 7.5, and 10. A pin-on-disc apparatus is pressed into service to conduct the wear test on the composite specimen. The results manifest that the wear rate of composite and frictional index of 10 vol.% of Habesha egg shell particles are 2.14 and 2.46 times better than 5 vol.% respectively. A decrement in frictional properties with an increase in eggshell content is observed along with an increment in the wear rate with the increase in sliding velocity and applied load. The L9 orthogonal array approach is followed to conduct the experiments, and a hybrid statistical approach of GRA-TOPSIS is applied to analyze the data and minimize wear objectives. ? The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024. corrected publication 2024.